Strategi Pemasaran Produk Usaha Mikro di Kabupaten Probolinggo Pada Masa Pandemi Covid-19 - Adil Abdillah (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2021)
This study aims to determine the constraints and problems in the marketing of micro business products in Probolinggo Regency so that it can be used in policy making by the local government for efforts to increase the marketing of the micro business. The object of this research is micro business actors in Probolinggo Regency. The analysis used is micro business data analysis, policy analysis, analysis of marketing potential and problems and analysis of micro business marketing strategy directions. Based on the analysis and identification of conditions in the field, the results of the marketing strategy for micro-enterprises in Probolinggo Regency are located in quadrant I, meaning that in this quadrant they face enormous market opportunities and internal strengths. The strategy set is Room A with Rapid Growth Strategy, which is a fast-flow growth strategy to show maximum development for certain targets and in a short time. The following is an action plan for marketing micro-enterprises in Probolinggo Regency.